Pengaruh peran Museum Pendidikan Nasional (Mupenas) UPI sebagai sumber belajar terhadap tingkat berpikir kronologis pengunjung (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
This study aimed to determine whether there is an influence on the role of Mupenas UPI, both in terms of education and other aspects of service, whether it influences the ability to think chronologically about visitors or not, especially in the national history/Indonesia education, further want to see whether the influence is positive or negative. The research method uses a correlational study. Data obtained through questionnaires and tests. Respondents were 2015 UPI history education students who were selected based on purposive sampling. Testing the hypothesis using the Spearman correlation test and linear regression test. The results show there is a positive relationship but very weak between the role of Mupenas UPI as a learning resource with the level of visitor’s chronological thinking measured by the level of ability to distinguish past, present, and future; level of ability to identify the temporal structure of historical narratives; the level of ability to set a sequence of historical narratives; level of ability to measure and calculate time units in history; and the level of ability explains change and continuity of time.
Keywords: Museum of National Education; Chronological Thinking